Effects of Dantrolene on Steps of Excitation-Contraction Coupling in Mammalian Skeletal Muscle Fibers - Szentesi, Péter (The Rockefeller University Press, 2001)
The effects of the muscle relaxant dantrolene on steps of excitation-contraction coupling were studied on fast twitch muscles of rodents. To identify the site of action of the drug, single fibers for voltage-clamp measurements, heavy SR vesicles for calcium efflux studies and solubilized SR calcium release channels/RYRs for lipid bilayer studies were isolated. Using the double Vaseline-gap or the silicone-clamp technique, dantrolene was found to suppress the depolarization-induced elevation in intracellular calcium concentration ([Ca(2)+](i)) by inhibiting the release of calcium from the SR. The suppression of [Ca(2)+](i) was dose-dependent, with no effect at or below 1 μM and a 53 ± 8% (mean ± SEM, n = 9, cut fibers) attenuation at 0 mV with 25 μM of extracellularly applied dantrolene. The drug was not found to be more effective if injected than if applied extracellularly. Calculating the SR calcium release revealed an equal suppression of the steady (53 ± 8%) and of the early peak component (46 ± 6%). The drug did not interfere with the activation of the voltage sensor in as much as the voltage dependence of both intramembrane charge movements and the L-type calcium currents (I(Ca)) were left, essentially, unaltered. However, the inactivation of I(Ca) was slowed fourfold, and the conductance was reduced from 200 ± 16 to 143 ± 8 SF(−1) (n = 10). Dantrolene was found to inhibit thymol-stimulated calcium efflux from heavy SR vesicles by 44 ± 10% (n = 3) at 12 μM. On the other hand, dantrolene failed to affect the isolated RYR incorporated into lipid bilayers. The channel displayed a constant open probability for as long as 30–50 min after the application of the drug. These data locate the binding site for dantrolene to be on the SR membrane, but be distinct from the purified RYR itself.